Comparative analyses of three pretreatments on color of kiwifruits during hot air drying - Xu, Ruzhen; Zhou, Xu; Wang, Shaojin (International Journal of Agricultural and Biological Engineering, 2020)
Color is one of the most important quality attributes for agricultural products due to its great influence on consumers’ appetite. Effects of pretreatments, including blanching with hot water, osmosis with sucrose solution, and soaking with ascorbic acid solution on the color of kiwifruit slices were investigated during hot air drying, and three models (i.e. zero-order, first-order and Weibull models) were used to describe the color change kinetics of soaking samples. The results illustrated that color parameters (L*, a* and b*) of dried kiwifruit slices were improved significantly by immersing in sucrose solution or ascorbic acid solution before drying, whereas immersing in hot water for long time led to severe color deterioration. For un-pretreated samples, the Weibull model was the best to describe change kinetics of L* and a* values with R2 =0.974 and 0.996, respectively, while the zero-order model was best for the changes of ΔE value (R2 =0.996). For samples immersed in 1% ascorbic acid solution for 15 min, change kinetics of L* and ΔE values were best fitted to zero-order models with R2 =0.988 and 0.972, respectively. ΔE of dried samples without pretreatment was 12.55, but decreased by approximately 16.33% when samples soaked in 1% ascorbic acid solution for 15 min before drying.Keywords: color, computer vision system, kinetic model, ascorbic acid, sucroseDOI: 10.25165/j.ijabe.20201302.5489Citation: Xu R Z, Zhou X, Wang S J. Comparative analyses of three pretreatments on color of kiwifruits during hot air drying. Int J Agric & Biol Eng, 2020; 13(2): 228–234.